Workshop on Scientific Article Writing Assisted by Artificial Intelligence for Teachers - Ahmad Khoiri; M Zainul Hafizi (Karuna: Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
This Workshop on Scientific Article Writing Assisted by Artificial Intelligence (AI) aimed to enhance the scientific writing competence of secondary school teachers by integrating AI-based tools ethically, reflectively, and productively. The program was held on March 16, 2024, at SMPN 21 Pontianak, involving fifteen teachers from various disciplines. The activity applied the Participatory Action Workshop (PAW) approach, emphasizing collaborative, experiential, and reflective learning through three key stages: orientation, writing practice, and individual mentoring. Participants were trained to use ChatGPT, Perplexity.ai, Humata.ai, and Research Rabbit to assist idea exploration, article structuring, and language editing in accordance with academic conventions. The results revealed significant improvements in teachers’ technical writing skills, understanding of publication ethics, and confidence in developing scholarly manuscripts. Each participant produced a draft article ready for further development and contributed to the formation of the AI-Based Teacher Writing Community of Pontianak as a post-program sustainability outcome. This activity demonstrates that short, intensive AI-assisted training can serve as an effective community engagement model to strengthen teacher professionalism in the digital era and contribute to achieving Sustainable Development Goal (SDG) 4: Quality Education